2015
DOI: 10.2514/1.a33215
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Absorber Ring Position and Cavity Length on Acoustic Damping

Abstract: The influence of axial position and cavity length of an absorber ring with grazing flow on damping of acoustic amplitudes in a rocket combustion chamber is experimentally investigated under nonreactive ambient temperature conditions. At the perforated inlet, high-bias flow velocities are present, providing strong damping. On the basis of power spectral densities gained from flow noise excitation, damping rates for the first transverse mode are derived using a Lorentzian profile fitting procedure. Results show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Up to now, only linear decay rates providing stability margin could be quantified, because the system identification (SI) methods used to process pressure data necessitate linearly stable conditions, e.g. [4] . Recently, it has been shown that one can take advantage of the presence of inherent turbulent combustion noise -whose effect on thermoacoustic dynamics has rarely been investigated, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, only linear decay rates providing stability margin could be quantified, because the system identification (SI) methods used to process pressure data necessitate linearly stable conditions, e.g. [4] . Recently, it has been shown that one can take advantage of the presence of inherent turbulent combustion noise -whose effect on thermoacoustic dynamics has rarely been investigated, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although up until two decades ago, the studies on damping device design for rocket engine combustion instabilities still dealt with QW as well as HH [8], nowadays most of the available literature concentrates on QW resonator rings [9]: in [10], the influence of the resonator length on the frequency of the engine acoustic modes is studied and [11] presents a graphical method based on a low-order network model to determine the stability of the system. The influence of such a QW resonator ring on the shape of the longitudinal and transversal [12] as well as azimuthal [13] modes, and on the stability margin of the engine [14] has also been studied.…”
Section: Introductionmentioning
confidence: 99%